A Review on Adverse Drug Reaction Detection Techniques - Nafea, Ahmed A.; AL-Mahdawi, Manar; AL-Ani , Mohammed M.; Omar , Nazlia (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
The detection of adverse drug reactions (ADRs) is an important piece of information for determining a patient’s view of a single drug. This study attempts to consider and discuss this feature of drug reviews in medical opinion-mining systems. This paper discusses the literature that summarizes the background of this work. To achieve this aim, the first discusses a survey on detecting ADRs and side effects, followed by an examination of biomedical text mining that focuses on identifying the specific relationships involving ADRs. Finally, we will provide a general overview of sentiment analysis, particularly from a medical perspective. This study presents a survey on ADRs extracted from drug review sentences on social media, utilizing and comparing different techniques.